Pertussis Toxin Nullifies the Depolarization of the Membrane Potential and the Stimulation of the Rapid Phase of 45Ca2+ Entry Through L-type Calcium Channels that are Produced by Follicle Stimulating Hormone in 10- to 12-Day-Old Rat Sertoli Cells - Jacobus, Ana P.; Loss, Eloísa S.; Wassermann, Guillermo F. (Frontiers in Physiology, 2010)
The aim of this study was to evaluate the effect of pertussis toxin (PTX) on the depolarizing component of the action of follicle stimulating hormone (FSH) on the membrane potential (MP) of Sertoli cells, which is linked to the rapid entry of Ca2+ into cells and to the Ca2+-dependent transport of neutral amino acids by the A system. This model allowed us to analyze the involvement of Gi proteins in the action of FSH in these phenomena. In parallel, using an inactive analog of insulin-like growth factor type I (IGF-1), JB1, and an anti-IGF-I antibody we investigated the possible mediating role of IGF-I on these effects of FSH because IGF-I is produced and released by testicular cells in response to stimulation by FSH and shows depolarization effects on MP similar to those from FSH. Our results have the following implications: (a) the rapid membrane actions of FSH, which occur in a time-frame of seconds to minutes and include the depolarization of the MP, and stimulation of 45Ca2+ uptake and [14C]-methyl aminoisobutyric acid ([14C]-MeAIB) transport, are nullified by the action of PTX and, therefore, are probably mediated by GiPCR activation; (b) the effects of FSH were also nullified by verapamil, an L-type voltage-dependent Ca2+ channel blocker; (c) wortmannin, an inhibitor of phosphoinositide 3-kinase (PI3K), prevented FSH stimulation of 45Ca2+ entry and [14C]-MeAIB transport; and (d) these FSH actions are independent of the IGF-I effects. In conclusion, these results strongly suggest that the rapid action of FSH on L-type Ca2+ channel activity in Sertoli cells from 10- to 12-day-old rats is mediated by the Gi/βγ/PI3Kγ pathway, independent of the effects of IGF-I.